Assessment of watershed health, vulnerability and resilience for determining protection and restoration Priorities. (December 2019) - Ahn, So-Ra; Kim, Seong-Joon
Abstract: The watershed health, vulnerability and recovery potential for determining protection and restoration priorities were assessed for the Han River basin (34, 148 km 2 ) in South Korea. Six components, including the watershed landscape, stream geomorphology, hydrology, water quality, aquatic habitat conditions, and biological conditions, were used to evaluate the watershed health (basin natural capacity). The Soil and Water Assessment Tool (SWAT) was utilized to examine the hydrology and water quality components in the study basin, which includes 237 sub-watersheds, three multipurpose dams, one hydroelectric dam, and three multifunction weirs. Four components, namely, the future impervious area, future climate conditions, future water use, and recent land cover changes were used to evaluate the watershed vulnerability to artificial stressors. We determined the protection and restoration priorities by evaluating and comparing the health and vulnerability of each sub-watershed. Sixty-seven sub-watersheds out of 237 were classified to have restoration priorities with high recovery potentials.